Manajemen Peningkatan Kompetensi Tenaga Pendidik pada Madrasah Tsanawiyah Negeri Olak Kemang - Nuraini Nuraini (Universitas Batanghari Jambi, 2019)
This Study aim to ind out the management of increasing the competence of teaching staff, supporting factors and inhibitors of improving the competence of teaching staff and management efforts to increase the competency of teaching staff at MTsN Olak Kemang, Jambi City. This study uses a qualitative approach, data collection is done by observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique, data analysis techniques carried out by data reduction, data presentation and verification / conclusion drawing, while checking the validity of the data is done by triangulation, talking with colleagues and holding member checks. The results of this study indicate that the management of improving the competency of teaching staff in the Jambi City Olak Kemang Madrasah Tsanawiyah still not optimal, among others: teachers do not fully want to take part in scientific writing training methods, have not attended scientific forums between teachers, are not used to reading up to two hours per day and also rarely visit learning resources and scientific institutions. Some of the supporting factors for increasing the competence of teaching staff in the Olak Kemang State Islamic Primary School in Jambi include: all teachers have S1 qualifications and have obtained certification certificates, efforts to improve the competence of educators can be done in several ways including: S1 advanced education to S2, training profession, taking part in the supervision program, empowering the MGMP, writing scientific journals, conducting research, taking part in an internship program and collaborating with colleagues.